2022
DOI: 10.1002/jso.26830
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid improves early postoperative mobilization in cancer patients undergoing endoprosthetic reconstruction

Abstract: Background and Objectives: Tranexamic acid (TXA) has been shown to decrease perioperative blood loss, transfusions, and cost in patients undergoing resection of aggressive bone tumors and endoprosthetic reconstruction. This study explored the effect of TXA administration on postoperative mobilization in these patients.Methods: This study included 126 patients who underwent resection of an aggressive bone tumor and endoprosthetic reconstruction; 61 patients in the TXA cohort and 65 patients in the non-TXA cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
3
0
1
Order By: Relevance
“…The use of intraoperative TXA in tumour surgery has increased substantially in recent years. 13,25 The results of the current study mirror those of Haase et al, 26 who found that intraoperative TXA improved postoperative rehabilitation and reduced hospital LOS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The use of intraoperative TXA in tumour surgery has increased substantially in recent years. 13,25 The results of the current study mirror those of Haase et al, 26 who found that intraoperative TXA improved postoperative rehabilitation and reduced hospital LOS.…”
Section: Discussionsupporting
confidence: 86%
“…The use of intraoperative TXA in tumour surgery has increased substantially in recent years. 13,25 The results of the current study mirror those of Haase et al, 26 who found that intraoperative TXA improved postoperative rehabilitation and reduced hospital LOS. Tourniquet use, TXA, and shorter operating time have been found to reduce blood loss and postoperative anaemia, which may be the common underlying factors affecting LOS.…”
Section: Discussionsupporting
confidence: 86%
“…These studies have demonstrated the efficacy of TXA in reducing blood transfusion rates with no apparent increase in postoperative complications, even in high‐risk patients 3–7 . While TXA has been shown to be safe for most orthopedic procedures, its use in orthopedic sarcoma surgery is not well‐established 26–28 . There is a theoretical concern for potentiating clotting in sarcoma patients due to their underlying prothrombotic state, which in part is caused by upregulation of the coagulation cascade 9 …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] While TXA has been shown to be safe for most orthopedic procedures, its use in orthopedic sarcoma surgery is not well-established. [26][27][28] There is a theoretical concern for potentiating clotting in sarcoma patients due to their underlying prothrombotic state, which in part is caused by upregulation of the coagulation cascade. 9 The use of TXA in our population of over 1000 sarcoma patients was based on surgeon preference rather than set criteria during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…In a SEER database study, Cranmer et al reported that chemotherapy did not improve survival for dedifferentiated chondrosarcoma 36 . In a comparative retrospective cohort study, Haase et al found that patients who underwent oncologic endoprosthetic reconstruction were more likely to walk and had longer endurance if tranexamic acid was administered perioperatively 43 . In a retrospective review by Lazarides et al, 149 patients were identified who underwent a surgical procedure for a primary bone tumor or a bone-invading soft-tissue tumor; the readmission rate within 90 days was 28.3% and was associated with female sex, higher tumor grade, and longer procedure duration 42 .…”
Section: Primary Bone Tumorsmentioning
confidence: 99%